Donor-acceptor-based two-dimensional polymer as a supercapacitor electrode with long cycling stability - Bhagyasree, T. M.; Puthiyaveetil, Priyanka Pandinhare; Kumar, Viksit; Asokan, Kiran; Sreekumar, K.; Babu, Sukumaran Santhosh (New Journal of Chemistry, 2023)
The high demand for energy and energy-storage devices urged organic 2D polymers as a potential candidate in this area. One of the major attractions of 2D polymers in electrochemical applications is their long cycling stability due to their rigid and porous structure. Herein, we developed a 2D polymer comprised of donor-acceptor units exhibiting reasonably good performance as a supercapacitor. The 2D polymer displayed a maximum specific capacitance of 218 F g-1 at a current rate of 0.1 A g-1, a higher power density of 4648.35 W kg-1, and an energy density of 7.05 W h kg-1. In a cycling stability test, it demonstrated a capacitance retention of 70% over 10 000 continuous charge-discharge cycles at a current rate of 2.5 A g-1. Such long cycling stability was attributed to the donor-acceptor units and the crystalline nature of the polymer. The sensible selection of the building blocks of the 2D polymers is crucial for the performance and hence provides scope for improvement. An organic donor-acceptor-based 2D polymer, a promising candidate for energy storage devices, displays a specific capacitance of 218 F g-1, a power density of 4648.35 W kg-1, an energy density of 7.05 W h kg-1, and a capacitance retention of 70% over 10 000 cycles.

Functionalized CNT-azobenzene-PVA-based self-healing aqueous gel as a conductive photo-responsive actuator - Narayanan, Aswini; Bhagyasree, T. M.; Torris, Arun; Babu, Sukumaran Santhosh (Journal of materials chemistry C, 2023)
Conductive gels have gained attention from researchers owing to potential applications in flexible displays, implantable medical devices, touch panels, wearable electronic skin, sensors, soft robotics, etc. Photo-responsive conductance switching gels can make their way into various applications, including contact-free remote-controlled manipulation of the materials, implantable synthetic organs, and optical switches. Herein, we report an aqueous gel with boronic acid containing azobenzene crosslinker as the light-responsive part that can undergo reversible cis-trans isomerization on irradiation with UV-vis light and catechol functionalized single-walled carbon nanotube as a conductive part producing a self-healing aqueous gel with PVA. The 3D crosslinked gel network formed through the formation of boronic ester and hydrogen bonding between hydroxyl and boronic acid groups was confirmed using scanning electron microscopy, X-ray microtomography, and rheological experiments. Rheology results show that gel is a viscoelastic material with immediate self-healing properties. The presence of functionalized SWCNT in the gel matrix enhances the stability and results in a conductivity of up to 3.5 S cm-1 with a loading of 5 wt%. The gel network exhibits a photoresponsive conductance switching from 10 to 60 mu A with UV and visible light irradiation, respectively. The molecular level motions during the isomerization of azobenzene lead to macroscopic dynamic changes that can find applications in soft actuators. The photoresponsive conductivity switching and dynamic movements of the films make the present material suitable for contact-free switching applications. Responsive conductive gels have gained attention owing to potential applications in flexible displays, implantable medical devices, touch panels, wearable electronic skin, sensors, soft robotics, and related areas.
Keywords: Cyclodextrins; Supramolecular Hydrogels

Scalable approach using a gC3N4 -covalent organic framework hybrid catalyst towards sustainable hydrogen production from seawater and wastewater - Asokan, Kiran; Bhagyasree, T. M.; Devasia, George; Krishnamurty, Sailaja; Solim, Sabah; Rueda, Lina; Al-Mohannadi, Dhabia M.; Al-Hashimi, Mohammed; Kakosimos, Konstantinos; Santhosh Babu, Sukumaran (CHEMICAL SCIENCE, 2024)